Enhancing Mobile Phones for People With Visual Impairments Through Haptic Icons: The Effect of Learning Processes. - Galdón-Conejo, Pedro María; Madrid-López, Rafael Ignacio; De-la-Rubia-Cuestas, Ernesto Jesús; Díaz-Estrella, Antonio; González, Lourdes (Taylor & Francis, 2013)
We report the results of a study on the learnability of haptic icons used in a system for incoming-call identification in mobile phones. The aim was to explore the feasibility of using haptic icons to create new assistive technologies for people with visual impairments. We compared the performance and satisfaction of users with different visual capacities (visually impaired vs. sighted) and using different learning processes (unimodal vs. multimodal). A better recognition rate and user experience were observed for the visually impaired than for sighted users and for multimodal rather than unimodal learning processes.
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/4976
Keywords: Ayudas técnicas para personas con discapacidad; Teléfonos móviles; Learnability; Mobile phones; Haptic icons; Tactile; Touch; Assistive technology